Benign diseases of the gastro-oesophageal junction - Nawacki, Łukasz G.; Głuszek, Stanisław; Kuder, Tadeusz (Medical Studies/Studia Medyczne, 2016)
Introduction: Benign diseases of the gastro-oesophageal junction are among the most frequent gastroenterological diseases, and include hiatal hernia of the diaphragm, gastro-oesophageal reflux, and oesophageal achalasia. The first two entities are frequently concomitant diseases; therefore, sometimes it is difficult to differentiate from which disease dominant symptoms are seen in a patient. Due to their anatomical location the diseases of the gastro-oesophageal junction may imitate complaints on the part of other organs and systems. A patient with sharp stabbing pain in the chest would probably be diagnosed for coronary, and not reflux disease. This is related with delayed diagnosis and implementation of the proper treatment. Aim of the research: To demonstrate our own experiences in surgical management of diseases of the gastro-oesophageal junction, the available methods, and outcomes of treatment. Material and methods : Retrospective analysis was performed of medical records of patients hospitalised in one research centre due to diseases of the gastro-oesophageal junction. The type of disease, age, gender, treatment method, duration of surgical procedure, duration of hospitalisation, and the outcome of treatment were taken into consideration. Results and conclusions: The outcomes of treatment were compiled in the form of a table. It was confirmed that in the case of diseases of the gastro-oesophageal junction, surgical treatment is a very important element, with a low number of complications and very good therapeutic effect.